Soviet State and Nomadic Peoples of Southern Russia: Social-Political Processes and Natural-Climatic Factors (1920s-1930s) - E. N. Badmaeva (Научный диалог, 2024)
This study examines Soviet national policy towards nomadic peoples during the 1920s1930s, a period   when   the   foundations of national-state building in the USSR were being laid and developed. The research focuses on a specific region — Southern Russia, one of the most multiethnic macro-regions of the country. The study investigates the implementation of socio-economic and national policies of the Soviet state in the territory of ethnic minorities such as the Kalmyks, Nogais, and Stavropol Turkmen. Common specific characteristics of the nomadic population are noted: religious fanaticism, social isolation, innate closedness. Eradicating these negative qualities among the Kalmyks, Nogais, Stavropol Turkmen, and integrating them into the all-Russian space required authorities to adopt a differentiated approach to working with each ethnic group. It is proven that by implementing the national policy of the Soviet state through solving urgent socio-economic problems of the Kalmyks, Nogais, and Stavropol Turkmen, the authorities were able to achieve at least two main objectives to some extent. The first objective was to lift the mentioned nomadic peoples out of socio-economic crisis, mainly through stimulating and developing agriculture, despite the challenging natural-climatic conditions of the region. The second objective was to ensure the transition of nomads to a settled way of life.